Evaluating the nexus between financial reporting metrics and share prices in Vietnam - Quang, Tran Anh; Ngan, Ninh Thi Thuy; Thanh, Nguyen Thi; Van, Hoang Khanh (Edelweiss Applied Science and Technology, 2026)
This study examines the value relevance of financial reporting metrics for the share prices of non-financial companies listed on the Ho Chi Minh City Stock Exchange. Drawing on a balanced panel of 356 non-financial firms over the 2020–2024 period, comprising 1,780 firm-year observations, the study estimates the impact of Earnings Per Share (EPS), Book Value Per Share (BVPS), book value of equity (BV), and Return on Equity (ROE) on share prices using Pooled OLS, Fixed Effects (FEM), and Random Effects (REM) estimators, with the FEM selected as the preferred specification. The results show that EPS exerts a positive impact on share prices that is statistically significant at the 1% level across all three models, whereas ROE, BVPS, and BV are weak or insignificant once firm-specific heterogeneity is controlled for. These findings indicate that earnings information dominates book-value measures in explaining equity prices, suggesting that Vietnamese investors price current profitability rather than historical accounting values. Accordingly, listed firms should enhance the quality and timeliness of earnings disclosures, investors can prioritize earnings-based indicators in equity valuation, and regulators should continue strengthening financial reporting transparency to support the informational efficiency of Vietnam's stock market.